(untitled) (Research, Society and Development, 2021)
Hemoparasitosis are diseases caused by different pathogens and spread by hematophagous vectors. In the midst of the veterinary clinical routine, it is possible to observe the importance of these diseases that affect different animals, presenting varied symptoms, from mild signs to more severe symptoms, which may even lead to the animal’s death. The objective of this study was to report the clinical cases of seven animals, inhabitants of a rural property in the city of Mineiros-GO, affected by several hemoparasitosis, namely: Dirofilaria immitis, Hepatozoon sp., Trypanosoma evansi, Babesia sp. and Ehrlichia sp., highlighting their clinical manifestations, findings laboratory tests and their treatments. The results of laboratory tests, together with the clinical signs presented, demonstrated how much hemoparasitosis can seriously affect animals with concomitant infections that are difficult to diagnose and have non-specific symptoms. This makes it essential to carry out examinations for a precise diagnosis, especially regarding the occurrence of these coinfections, thus enabling an adequate and effective treatment for the reestablishment of the animals’ health and well-being.